BANKING MARKET DISCIPLINE IN INDONESIA AN EMPIRICAL TEST ON CONVENTIONAL AND ISLAMIC BANK - Hasan Hasan; Eduardus Tandelilin (Faculty of Economics and Business, Universitas Gadjah Mada, 2012)
A sound banking system is vital in supporting a sound and strong economy. One of the important pillars of a sound banking system is market discipline, which is the reaction ofthe market makers on the risks taken by banks as a form of supervision and discipline. The objectives of this paper are to examine: (i) the existence of market discipline by depositors in the deposit insurance era by the Indonesia Deposit Insurance Corporation (LPS); (ii) the difference in market discipline by depositors before and after the policy of increasing the value of deposit covered; (iii) the difference between market discipline by depositors of Islamic banks with conventional banks. The data used are annually individual bank data from the Indonesian Banking Directory (DPI) in 2005-2009. The dependent variable is the change in deposits, which is used as proxy for market discipline in t period. The independent variables used are CAR, APB, NIM, and LDR as proxy of financial risk/fundamental condition of the bank in t-1 period. The result indicates the existence ofmarket discipline in Indonesia and also shows that market discipline is detected stronger in the period 2005-2007 than the period 2008-2009. This study also indicates that marketdiscipline by depositors of Islamic banks are stronger than those of conventional.Keywords: market discipline, deposit insurance, Islamic and conventional banks.